The transformative power of the copy: a transcultural and interdisciplinary approach - Forberg, Corinna; Stockhammer, Philipp (Heidelberg studies on transculturality, 2017)
This volume offers a fresh perspective on the copy and the practice of copying, two topics that, while the focus of much academic discussion in recent decades, have been underrepresented in the discourse on transculturality. Here, experts from a wide range of academic disciplines present their views on the copy from a transcultural perspective, seeking not to define the copy uniformly, but to reveal its dynamic and transformative power. The copy and the practice of copying are thus presented as constituents of transculturality via thought-provoking contributions on topics spanning time periods from antiquity to the present, and regions from Asia to Europe. In so doing, these contributions aim to create the basis for a novel, interdisciplinary discourse on the copy and its transcultural impact throughout history
Keywords: Aufsatzsammlung; Konferenzschrift; Europa; Interkulturalität; Kopie; Asien